Changes in selected physical, motor performance and anthropometric components of university-level rugby players after one microcycle of a combined rugby conditioning and plyometric training program - Pienaar, C.; Coetzee, B. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to determine the effects of a microcycle (4 weeks) combined rugby conditioning plyometric compared with a nonplyometric rugby conditioning program on selected physical and motor performance components and anthropometric measurements of university-level rugby players. Players (18.94 ± 0.40 years) were assigned to either a control (n = 16) or experimental group (n = 19) from the U/19 rugby teams of the North-West University (South Africa). Twenty-six direct and indirect anthropometric measurements were taken, and the players performed a battery of 5 physical and motor performance tests before and after a microcycle (4 week) combined rugby conditioning plyometric (experimental group) and a nonplyometric rugby conditioning program (control group). The dependent t-test results showed that the control group's upper-body explosive power decreased significantly, whereas the stature, skeletal mass, and femur breadth increased significantly from pre- to posttesting. The experimental group showed significant increases in wrist breadth, speed over 20 m, agility, and power and work measurements of the Wingate anaerobic test (WAnT). Despite these results, the independent t-test revealed that speed over 20 m, average power output at 20 seconds, relative work of the WAnT, and agility were the only components of the experimental group that improved significantly more than the control group. A microcycle combined rugby conditioning plyometric program therefore leads to significantly bigger changes in selected physical and motor performance components of university-level rugby players than a nonplyometric rugby conditioning program alone. Based on these findings, coaches and sport scientists should implement 3 weekly combined rugby conditioning plyometric programs in rugby players' training regimens to improve the players' speed, agility, and power.